ANALISIS TENTANG KARAKTER YANG BAIK DI SMA NEGERI 1 PEKANBARU - Fitra Annisa; Sri Erlinda; Jumili Arianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is motivated by problems that arise during observations made by researchers, namely students in SMA Negeri 1 Pekanbaru. still the lack of students and students who obey school rules is also a form of character that is not good, always comes late and does not have the discipline ofself and responsibility. One example of cases of moral decline in students when children are reprimanded by the teacher because they make mistakes, they instead tend to fight the teacher with inappropriate actions. The formulation of the problem in this research is What is a Good Character in SMA Negeri 1 Pekanbaru? The purpose of this research is to find out how good character is at SMA Negeri 1 Pekanbaru. This research was conducted at SMA Negeri 1 Pekanbaru in May -October 2019. This study used a quantitative descriptive method. The population in this study were all students in SMA Negeri 1 Pekanbaru, amounting to 948 people from classes X, XI, XII. The sample in this study was taken using a proportional sampling technique with a total of 94 people. Data in this study were collected through observation, questionnaires, interviews, and documentation. The results of this study indicate that Good Character is as much as 89% which means